Offshore Earthquakes Do Not Influence Marine Mammal Stranding Risk on the Washington and Oregon Coasts - Rachel A. Grant; Anna Savirina; Will Hoppitt (Animals, 2018)
The causes of marine mammals stranding on coastal beaches are not well understood, but may relate to topography, currents, wind, water temperature, disease, toxic algal blooms, and anthropogenic activity. Offshore earthquakes are a source of intense sound and disturbance and could be a contributing factor to stranding probability. We tested the hypothesis that the probability of marine mammal stranding events on the coasts of Washington and Oregon, USA is increased by the occurrence of offshore earthquakes in the nearby Cascadia subduction zone. The analysis carried out here indicated that earthquakes are at most, a very minor predictor of either single, or large (six or more animals) stranding events, at least for the study period and location. We also tested whether earthquakes inhibit stranding and again, there was no link. Although we did not find a substantial association of earthquakes with strandings in this study, it is likely that there are many factors influencing stranding of marine mammals and a single cause is unlikely to be responsible. Analysis of a subset of data for which detailed descriptions were available showed that most live stranded animals were pups, calves, or juveniles, and in the case of dead stranded mammals, the commonest cause of death was trauma, disease, and emaciation.